Pengaruh Sandblasting Dan Limbah Gypsum Sebagai Bahan Campuran Beton - Daniel Surgawi; Frans Phengkarsa; Suryanti Rapang Tonapa (Paulus Civil Engineering Journal, 2022)
Normal concrete is concrete with a compressive strength value of 15-40 MPa.this study aims to find out the workability of fresh concrete with the addition of sandblasting 10% and gypsum waste variations of 0%, 2%, 4%, 6% in concrete mixtures. Samples with a cylindrical shape with dimensions of 15cm x 30cm total 12 pieces, as well as beams with dimensions of 15cm x 15cm x 60cm total of 3 pieces. In the strong press test process obtained numbers 26,020, 24,027, 23,469 and 21,161 Mpa. Testing tensile strengths of 2,712, 2,098, 1,745, and 1,462 Mpa. Tests of 4,119, 3,793, 3,585, and 3,230 MPa. Elasticity modulus testing of 22384, 20497, 20025, and 19132 MPa. The results showed that gypsum waste cannot be used as a concrete quality mixture material.